2016
DOI: 10.5125/jkaoms.2016.42.6.345
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the osseointegration of implants in dog mandibles according to the implant surface treatment

Abstract: ObjectivesThis study compared the impact of implant surface treatment on the stability and osseointegration of implants in dog mandibles.Materials and MethodsSix adult dogs received a total of 48 implants that were prepared using four different surface treatments; resorbable blast media (RBM), hydroxyapatite (HA), hydrothermal-treated HA, and sand blasting and acid etching (SLA). Implants were installed, and dogs were separated into 2- and 4-week groups. Implant stability was evaluated via Periotest M, Osstell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Different manufacturers develop other types of surfaces. In the case of BioHorizons, the RBT ® surface is based on sandblasting with synthetic resorbable bioceramic particles, such as titanium dioxide, hydroxyapatite, or tricalcium phosphate particles, to make the surface rougher [24,25]. The presence of these particles, which some of them are naturally part of the mineral bone phase, seeks to improve and accelerate the osseointegration phase [10].…”
Section: Discussionmentioning
confidence: 99%
“…Different manufacturers develop other types of surfaces. In the case of BioHorizons, the RBT ® surface is based on sandblasting with synthetic resorbable bioceramic particles, such as titanium dioxide, hydroxyapatite, or tricalcium phosphate particles, to make the surface rougher [24,25]. The presence of these particles, which some of them are naturally part of the mineral bone phase, seeks to improve and accelerate the osseointegration phase [10].…”
Section: Discussionmentioning
confidence: 99%
“…To increase osseointegration during implant placement, research has concentrated on the surface modification of implants, and morphological analyses have looked at the thread pattern in close interaction with the bone's surface [ 13 ]. The morphological alongside chemical characteristics of the implant, such as the charge of the surface, protein absorption, wettability, cell and tissue growth on the surface, and cell-surface interactions according to Ratner and Porter [ 14 ], are significant factors that influence how the surface interacts with the bioactive materials. According to Davies' research [ 15 ], platelet activation at the outermost layer of the implant leads to an interaction between osteocytes and the implant interface that promotes the production of new bone and increases bone conduction continuity.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that UV irradiation of Korean implants prior to implantation in dogs did not improve the mean insertion torque or the BIC values in all studied groups at 4 and 12 weeks post implantation [ 7 ]. Alternatively, resorbable blast media (RBM) and sandblasted and acid-etched (SLA) surface implants were found to be safely preferable with proper case selection [ 8 ]. Furthermore, UMUT-SLA and tricalcium phosphate/hydroxyapatite (TCP/HA) surfaces improved the BIC value, and induced accumulated bone density during the osseointegration period (six weeks) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%